2020
DOI: 10.22541/au.160616173.35255142/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recognition and Treatment of Severe COVID-19 in Pregnancy: Lessons from a Cohort of 69 Infected Women and an Evidence-Based Guideline

Abstract: Objectives: To determine clinical and laboratory features of pregnant woman with COVID-19 who require respiratory support. To recommend a management strategy that optimises maternal and fetal outcomes. Design: An observational cohort study of 7000 maternities between 1st March and 1st July 2020. Setting: Five maternity centres across a maternal medicine network in north-central London, UK Population: 69 pregnant women with confirmed acute SARS-COV2 Methods: Review of electronic healthcare records Main Outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Gestational age ranged from 17 to 37 weeks. Four patients were at 17-22 weeks of gestation, 14 were at 24-28, 17 were at [29][30][31][32][33]15 were at 34-36, and 2 patients were at >37 weeks of gestation. The mean age of the patients was 31.9 ± 4.79 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gestational age ranged from 17 to 37 weeks. Four patients were at 17-22 weeks of gestation, 14 were at 24-28, 17 were at [29][30][31][32][33]15 were at 34-36, and 2 patients were at >37 weeks of gestation. The mean age of the patients was 31.9 ± 4.79 years.…”
Section: Resultsmentioning
confidence: 99%
“…Lymphopenia has been identified as the most distinctive predictive parameter [32][33][34]. In a study by Lombardi et al, lymphocyte values at admission correlated with the oxygen need.…”
Section: Discussionmentioning
confidence: 99%
“…Yuming et al [ 18 ] reported that the main laboratory findings were lymphopenia and elevated CRP in 146 pregnant women, 5.5% of which were severe. In their research, Scott et al [ 19 ] studied 69 COVID - 19 positive pregnant women, 15 of which required respiratory support, and they reported that the lymphocyte rate was lower in those who required respiratory support; however, WBC, neutrophil and PLT rates were similar. CRP was elevated in 63 patients during hospitalisation; however, there was no statistically significant difference between the groups.…”
Section: Discussionmentioning
confidence: 99%